Photoprotection issues. (October 2011) - Pacifico, Alessia; Leone, Giovanni; Picardo, Mauro
UV radiation causes DNA damage, inflammation, erythema, sunburn, immunosuppression, photoaging, gene mutations and skin cancer. Genetic alterations in the p53 tumor suppressor gene play a pivotal role in skin cancer development. p53, also known as 'guardian of the genome'', acts by promoting DNA repair and elimination of cells with an excessive DNA damage. Chronic UV exposure inactivates DNA repair mechanisms leading to the onset of p53 mutations. Keratinocytes with p53 mutations acquire a growth advantage because of their increased resistance to apoptosis and to cell death. Apoptosis-resistant keratinocytes undergo clonal expansion that, over the years, may lead to formation of actinic keratoses and squamous cell carcinomas. Although UV-induced p53 mutations arise years before the development of skin cancer, interruption of UV exposure can still result in skin tumor development. Sunscreens used in Europe cover the entire UV spectrum, but there are still several aspects to optimize: photoinstability, penetration and protection against infra-erythemal effects. The regular use of sunscreens may decrease the development of precancerous lesions, the recurrence of squamous-cell carcinomas and the onset of nevi in children. It is very important to consider the chemical and physical properties of sunscreens as well as their modality of application. Usually, sunscreens are used at a much lower quantity per surface area than the amount used by manufacturers to assess the sun protection factor and they are often not adapted to individual skin type and situation, and are neither applied at a sufficient frequency, nor in a homogeneous way. In the last few years, modern techniques allowed the introduction of liposomes containing DNA repair enzymes – in order to increase DNA repair after UV exposure – and purified DNA repair enzymes, such as photolyase extract, both formulated into cosmetic suncare preparations and already marketed in aftersun lotions or sunscreens together with UV filters.